kiyam - McIlwraith , Naomi (Athabasca University Press, 2012)
Through poems that move between the two languages, McIlwraith explores the beauty of the intersection between n?hiyaw?win, the Plains Cree language, and English
English
Keywords: Language; Poems; Cree